Modelling analysis and optimisation of porous structural scaffolds for human bones - Xue Hui; Song Xiujuan; Zhang Guoliang; Xu Shubo; Zhang Weihai; Sun Siyu; Pan Yuefei; Li Jianing; Ren Guocheng (International Journal for Simulation and Multidisciplinary Design Optimization)
Two different types of unit structure models, ortho tetrahedral and hexahedral, are established, and a series of different porosities are obtained by controlling the parameters such as rod diameter and rod length, and the porous structure can be obtained by stacking the unit structure in an orderly manner in the three-dimensional space, and then finite element simulation and analysis are carried out by simulating compression experiments using Ansys to obtain the equivalent stresses, deformation maps and data, and the elastic modulus, which is close to that of the human hip bone, is calculated to investigate the mechanical properties under different porous structures and different porosities. The modulus of elasticity was calculated to be close to that of the human hip bone, and the mechanical properties were investigated under different porous structures and different porosities. The Fluent module is also used to simulate the fluid field, and the pressure and velocity maps of the fluid inside the two porous structures are obtained for comparative and comprehensive analyses. From the simulation of the created porous model, it is learnt that, for the same structure, with the increase of porosity, the equivalent force and deformation increase and the elastic modulus decreases significantly; for the same porosity, under the same loading environment, the longitudinal deformation of the hexahedron is smaller than that of the tetrahedron, its equivalent force is much lower than that of the tetrahedron, and it has suitable elastic modulus. Its strength is higher than that of the tetrahedron when under pressure. When the fluid flows in the hexahedron, the hexahedral structure is less compressed than the ortho tetrahedral structure, and the flow rate is more suitable for the blood flow rate in the human body.